Forest landscape ecology and global change: an introduction - Azevedo, João (2014)
Forest landscape ecology examines broad-scale patterns and processes and their interactions in forested systems and informs the management of these ecosystems. Beyond being among the richest and the most complex terrestrial systems, forest landscapes serve society by providing an array of products and services and, if managed properly, can do so sustainably. In this chapter, we provide an overview of the field of forest landscape ecology, including major historical and present topics of research, approaches, scales, and applications, particularly those concerning edges, fragmentation, connectivity, disturbance, and biodiversity. In addition, we discuss causes of change in forest landscapes, particularly land-use and management changes, and the expected structural and functional consequences that may result from these drivers. This chapter is intended to set the context and provide an overview for the remainder of the book and poses a broad set of questions related to forest landscape ecology and global change that need answers.